2018
DOI: 10.1177/1947603517752056
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Analysis of the Distal Femoral Condyle Articular Cartilage Surface: Adequacy of the Graft from Opposite Condyles of the Same or Different Size for the Osteochondral Allograft Transplantation

Abstract: Objective To analyze the topography of the opposite condyle to treat focal femoral condyle articular defects with an osteochondral allograft (OCA). Design Three groups were created: Group 1, same condyle with same width; Group 2, opposite condyle with same width; Group 3, opposite condyle with different width. Computed tomography (CT) of 22 cadaveric femoral hemi-condyles was used to create 3-dimensional CT models that were exported into point-cloud models. Three zones of the donor condyle (anterior, middle, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…This growing body of literature evaluating contour, topography, and graft matching of OCAs in various cadaveric studies supports the width measurement of the femoral condyle or tibial plateau as the standard for size matching OCAs. 7,58,80,88 The experts strongly agree that femoral condyles can be adequately size matched using condylar and/or tibia width measured on radiographs with magnification correction or magnetic resonance imaging/computed tomography. A recent clinical study showed that graftrecipient anteroposterior mismatch was not associated with OCA failure or patient outcomes, suggesting that anteroposterior length mismatch is not an absolute contraindication for graft acceptance.…”
Section: Graft Matchingmentioning
confidence: 97%
See 1 more Smart Citation
“…This growing body of literature evaluating contour, topography, and graft matching of OCAs in various cadaveric studies supports the width measurement of the femoral condyle or tibial plateau as the standard for size matching OCAs. 7,58,80,88 The experts strongly agree that femoral condyles can be adequately size matched using condylar and/or tibia width measured on radiographs with magnification correction or magnetic resonance imaging/computed tomography. A recent clinical study showed that graftrecipient anteroposterior mismatch was not associated with OCA failure or patient outcomes, suggesting that anteroposterior length mismatch is not an absolute contraindication for graft acceptance.…”
Section: Graft Matchingmentioning
confidence: 97%
“…58,80 0 0 0 0 2 2 D A contralateral OCA can be utilized for single plug restoration up to 25 mm in diameter. 20,58,80,83,88 0 0 1 0 4 5 C Femoral condylar OCAs can be adequately size matched using condylar and/or tibial width measured on radiographs with magnification marker or MRI/CT. 20,82 0 respondents agreed that rehabilitation after OCA reconstruction of the patellofemoral region should include weightbearing as tolerated in conjunction with extension bracing (up to 6 weeks).…”
Section: Rehabilitation and Return To Sportsmentioning
confidence: 99%
“…Second, only 20-mm defects were investigated. Prior work 42,45,46 has shown that LFC allografts for 25-mm centrally located lesions do not replicate the native surface geometry as well as for 20-mm lesions. However, since 75% of harvested MFCs are <25 mm in the mediolateral direction (JRF Ortho, oral personal communication, April 2017), larger lesions tend to extend more in the anteroposterior direction.…”
Section: Discussionmentioning
confidence: 99%
“…Contralateral LFC allografts have shown an excellent surface contour match when compared with MFC grafts for defects of 20 mm in diameter. 29 Yanke et al 42,45,46 have corroborated these findings with computer modeling, concluding that LFC allografts provide an acceptable topography match for 20-mm MFC defects, but the ability to match the topography decreases as the graft size increases to 25 mm. With a good surface topography match, acceptable clinical outcomes can be achieved.…”
mentioning
confidence: 86%
See 1 more Smart Citation